TOBACCO INDUSTRY LABOR MANAGEMENT COMMITTEE STATEMENT OF OPERATING CASH RECEIPTS AND DISBURSEMENTS AND OPERATING CASH BALANCE FOR THE SIX MONTH PERIOD ENDING 920630 (Tufts Archival Research Center, 2007)
Statement of cash receipts and disbursements from the Tobacco Industry Labor Management Committee for a six month period ending June 30, 1992. Includes professional fees and contributions in support of other organizations.